African Dimension of the Belt and Road Initiative - Kaczmarek, Filip (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2019)
The research purpose of this paper is to examine the role of the BRI in China-Africa relations and the mutual interdependence between the BRI and other forms of Chinese presence in Africa. In order to attain this goal, the method of analysis of secondary data will be employed regarding concluded agreements, trade exchange, Official Development Assistance (ODA), foreign direct investment (FDI), debt, instruments of soft power and plans for the future. The analysis allows the several conclusions to be drawn. The BRI is so flexible that it can be extended in a relatively simple way and in a short period to other African countries. The BRI is the structuring factor in China’s strategic approach to Africa and can give new impetus to Chinese trade, investment and contracts in Africa. The former institutional co-operation framework that encompassed the whole of Africa was very general and did not result in the identification of such concrete sec- toral priorities as is the case with the BRI. The Initiative has exerted influence on China’s policy in Africa. There is no doubt that the Initiative’s core task in Africa is infrastructure connectivity, but one of the tasks proposed for the future is industrial relocation. If this task is accomplished, it may be fundamental for Africa’s development.

Celem tego artykułu jest zbadanie roli Inicjatywy Pasa i Drogi (Nowego Jedwabnego Szlaku – BRI) w stosunkach między Chinami i Afryką oraz wzajemnej zależności między inicjatywą BRI a innymi formami chińskiej obecności w Afryce. Aby osiągnąć ten cel, zastosowano metodę analizy danych wtórnych dotyczących zawartych umów, wymiany handlowej, oficjalnej pomocy rozwojowej (ODA), bezpośrednich inwestycji zagranicznych (FDI), długu, instrumentów miękkiej siły i planów na przyszłość. Analiza pozwala wyciągnąć kilka wniosków. Inicjatywa BRI jest tak elastyczna, że może stosunkowo łatwo i szybko zostać rozszerzona na inne kraje afrykańskie. Inicjatywa BRI jest czynnikiem kształtującym strategiczne podejście Chin do Afryki i może nadać nowy impuls chińskiemu handlowi, inwestycjom i kontraktom w Afryce. Dawne ramy współpracy instytucjonalnej, które obejmowały całą Afrykę, były bardzo ogólne i nie doprowadziły do określenia takich konkretnych priorytetów sektorowych, jak ma to miejsce w przypadku inicjatywy BRI. Inicjatywa wywarła wpływ na chińską politykę w Afryce. Nie ulega wątpliwości, że głównym zadaniem Inicjatywy w Afryce jest integracja infrastruktury, a jednym z zadań zaproponowanych na przyszłość jest relokacja przemysłowa. Jeśli plany te zostaną zrealizowane, mogą mieć fundamentalne znaczenie dla rozwoju Afryki.
Afrykański wymiar Inicjatywy Pasa i Drogi
Keywords: Africa; China; Belt and Road Initiative; Afryka; Chiny; Inicjatywa Pasa i Drogi